Generalized Contraflow for Evacuation Planning Problem - Pyakurel, Urmila (Journal of Nepal Mathematical Society, 2018)
The research in evacuation planning has been very much motivated due to the rapidly increased number of disasters world wide. It supports to remove the evacuees from dangerous areas to safe areas. Contraflow reconfiguration during evacuation make traffic smooth by reversing the required road directions from dangerous areas to safe areas that improve both flow and speed significantly. On lossy network, the generalized maximum dynamic contraflow and generalized earliest arrival contraflow problems have been solved efficiently with pseudo-polynomial time. This paper focuses in analytical solutions on generalized contraflow for evacuation planning problem. The problems are considered on two terminal lossy networks. We solve the generalized maximum static contraflow problem in pseudo-polynomial time and compute its approximation solution in polynomial time. Moreover, we present a fully polynomial time approximation scheme (FPTAS) to compute an approximate generalized maximum dynamic contraflow solution.